Accounting systems : procedures and methods - Gillespie, Cecil (Englewood Cliffs, N.J. : Prentice-Hall ; New Delhi : Prentice-Hall of India, 1971)
Explains how to make a survey of business, select the methods, design the system or procedure and prepare system reports or manual.
Includes bibliographical references and index.
kjo 15/01/2019
Loans
Keywords: Accounting; Accounting machines